Influence of low operating temperature on biomass yield during anaerobic treatment of chocolate confectionery wastewater in a pilot-scale UASB reactor. (August 2022) - Esparza-Soto, M.; Alcaraz-Ibarra, S.; Lucero-Chávez, M.; Mier-Quiroga, M.; Fall, C.
Abstract: It has been found that biomass yield (Yobs ) increases as operating temperature decreases in batch reactors fed with synthetic substrate; nevertheless, there is a gap in literature about this phenomenon in pilot-scale reactors treating real industrial wastewaters, such as from the chocolate confectionery industry. Therefore, the effect of low operating temperature on the Yobs during the anaerobic treatment of chocolate confectionery wastewater (CCWW) was studied. In this research, the CCWW was treated in a 244-L pilot-scale upflow anaerobic sludge blanket reactor, which was operated for 275 days at short hydraulic retention time (6 h), medium total applied organic loading rates (OLR T appl ) (6.7–11.6 kg-total chemical oxygen demand (COD T /m 3 /d)), and low operating temperature (14–20 °C). The COD removal efficiency ranged from 70 to 90 % and the methane production rate varied between 230 and 393 L-CH4 /d at standard temperature and pressure (84 % of methane in biogas). The results showed that Yobs was higher at 14 °C [0.20 g-volatile suspended solids/g-removed COD (g-VSS/g-CODrem )] than at 20 °C (0.15 g-VSS/g-COD). Also, high Yobs values lead to a larger anaerobic biomass washout in the reactor effluent. The anaerobic biomass washout was also influenced by the presence of sodium in CCWW, the high OLR T appl and the low operating temperature, which made difficult the solids-liquid separation. Highlights: A pilot-scale UASB reactor efficiently treated chocolate confectionery wastewater. Yobs was higher at 14 °C (0.20 g-VSS/g-CODrem ) than at 20 °C (0.15 g-VSS/g-CODrem ). High quality biogas (84 % of methane) was daily produced (230–393 L-CH4 /d). 74 % of the theoretical methane production was recovered in the UASB reactor. High OLR and the presence of Na + cations led to excessive sludge wash-out.